UNIT 9.26 Huntington Disease: Molecular Diagnostics Approach. (6th October 2015) - Bastepe, Murat; Xin, Winnie
Abstract : Huntington disease (HD) is caused by expansion of a CAG trinucleotide repeat in the first exon of the Huntingtin ( HTT ) gene. Molecular testing of Huntington disease for diagnostic confirmation and disease prediction requires detection of the CAG repeat expansion. There are three main types of HD genetic testing: (1) diagnostic testing to confirm or rule out disease, (2) presymptomatic testing to determine whether an at‐risk individual inherited the expanded allele, and (3) prenatal testing to determine whether the fetus has inherited the expanded allele. This unit includes protocols that describe the complementary use of polymerase chain reactions (PCR) and Southern blot hybridization to accurately measure the CAG trinucleotide repeat size and interpret the test results. In addition, an indirect linkage analysis that does not reveal the unwanted parental HD status in a prenatal testing will also be discussed. © 2015 by John Wiley & Sons, Inc.